Dança, identidade, universalidade: as danças circulares no grupo Mana-Maní, em Belém, Brasil - CASTRO, Fábio Fonseca de (Universidade Caxias do Sul, 2022)
The article takes an ethnographic approach over circular dances developed by Mana Mani, a cultural group from Belém (Brazil). We want to discuss how the circular dances, a booming cultural practice in contemporary societies, contribute to the formation of identity. We discuss, particularly, the production of the empathic social bond as a factor for the constitution of political and ethical references in the identitarian typification process. Accordingly, we look into how the proposed merger between universal and local is inserted among the contemporary cultural practices on hybrid cosmopolitan senses. We also seek to discuss how traditional dances and musicality of traditional Amazonian populations are appropriated by the group and become communal ideals and values and how they produce political and ethical directions and meanings to the to the local, in his dialogue with the universal.